2016
DOI: 10.4081/xeno.2016.5660
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of acute exposure of industrial chemicals and pesticides on the survival of fish (Tilapia guineensis) and earthworms (Aporrectodea longa)

Abstract: Ecotoxicological effects of industrial chemicals (Rig wash, Oil eater, Nalco, Glycol™) and pesticides (Propoxur, Deltamethrin, Atrazine, Furadan) on Tilapia guineensis (fish) and Aporrectodea longa (earthworms) were tested using the Organisation for Economic Cooperation and Development (OECD) # 203 and 207 protocols. The water and soil ratings indicate that the test chemicals were toxic to the organisms. The estimated 96 hour lethal concentration LC 50 values for Rig wash, Oil eater, Nalco EC1304A/COT 505, Gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Since these chemicals are commonly used in crude oil production, their release into the aquatic environment can pose significant ecological problems, particularly for fish in affected regions. Ogeleka et al (2016) reported that industrial chemicals in Tilapia guineesis can cause fish species death, leading to a reduction or elimination of potentially reproductive species.…”
Section: Discussionmentioning
confidence: 99%
“…Since these chemicals are commonly used in crude oil production, their release into the aquatic environment can pose significant ecological problems, particularly for fish in affected regions. Ogeleka et al (2016) reported that industrial chemicals in Tilapia guineesis can cause fish species death, leading to a reduction or elimination of potentially reproductive species.…”
Section: Discussionmentioning
confidence: 99%
“…Ogeleka et al [6] reported concentrations of the pesticides, propoxur, deltamethrin, atrazine, and furadan that caused the death of fish and earthworms in aquatic and terrestrial environments. Pesticides find their way to aquatic and terrestrial ecosystems through aerial drifts and runoffs after rains, where they exert harmful effects on aquatic bodies such as fish and frogs.…”
Section: Introductionmentioning
confidence: 99%